2011
DOI: 10.1007/978-3-642-20757-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evaluation of HTTP Adaptive Streaming under Vehicular Mobility

Abstract: Abstract. Adaptive streaming is a promising technique for delivering a high-quality video streaming experience. In this technique, the streaming bit-rate is constantly adjusted in accordance to the variations in the underlying network bandwidth conditions. A popular instantiation of this approach is to extend traditional HTTP-based streaming. While several such implementations are widely available, it is unclear how they perform under a typical high-speed vehicular environment, wherein the wireless bandwidth v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 8 publications
1
43
0
Order By: Relevance
“…The ClosetoEdge video (43,24) is from a documentary and is mostly shot with a handheld camera and features varying characteristics. The Rollingstone video (45,42) is from a concert recording, where the lead singer moves around a lot and the video has some sudden scene changes. The News (49,23) video is from a TV news broadcast and has static scenes with one/two standing/sitting people, some scenes with moving background and some scenes without reporters with more motion and panning.…”
Section: Subjective Experiments Of Video Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The ClosetoEdge video (43,24) is from a documentary and is mostly shot with a handheld camera and features varying characteristics. The Rollingstone video (45,42) is from a concert recording, where the lead singer moves around a lot and the video has some sudden scene changes. The News (49,23) video is from a TV news broadcast and has static scenes with one/two standing/sitting people, some scenes with moving background and some scenes without reporters with more motion and panning.…”
Section: Subjective Experiments Of Video Qualitymentioning
confidence: 99%
“…The adaptation is made possible through the provision of multiple bitrate copies in segments of the video being transmitted from the server. The usage of adaptive streaming has been notably observed to be useful in the reduction of video stalling that might occur due to bandwidth constraints [45]. A client might prefer to switch to lower quality video instead of experiencing a halt (buffering) in the video playback.…”
Section: Introductionmentioning
confidence: 99%
“…The work in [9] has analysed the trade-off between those two impairments directly. In the context of HAS, studies on optimal segment length and buffer size [24], also identified initial delays as an impairment type to be considered. Concerning stalling events during the video playout, it is generally assumed that they decrease QoE severely and that quality adaptation performs better.…”
Section: Related Workmentioning
confidence: 99%
“…The type of encoder immensely influences QoE and is applicable for scalable video codecs (SVC) that inspect streaming using H.264/SVC with wavelet-based coding. Authors of [70,71,72,73,74] introduced a new approach to encode and segment video information for adaptively streaming H.264 video. They also achieved up to 30% reduction in encoding bitrate while maintaining the same or higher quality of video.…”
Section: Network Protocols and Algorithmsmentioning
confidence: 99%